Report from the Inside: The CERD Committee's Review of the Foreshore and Seabed Act 2004 - Charters, Claire; Erueti, Andrew (Victoria University of Wellington Law Review, 2005)
This paper describes, from the perspective of the advocates for Māori claimants, the substance of submissions to, and process followed by, the United Nations Committee on the Elimination of Racial Discrimination in determining that the Foreshore and Seabed Act 2004 discriminates against Māori. The paper has a number of functions: it illustrates that, contrary to the Prime Minister's suggestions, the process followed by the Committee was robust; provides much needed comment on the Committee's early warning and urgent action procedure; should be useful to other individuals or groups seeking to challenge legislation in international fora; and, finally, sheds light on the Committee's succinct decision by placing it within the context from which it emerged.